2019
DOI: 10.3390/v12010036
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Different Huh7 Variants Reveals Novel Hepatitis C Virus Host Factors

Abstract: Chronic Hepatitis C virus (HCV) infection still constitutes a major global health problem with almost half a million deaths per year. To date, the human hepatoma cell line Huh7 and its derivatives is the only cell line that robustly replicates HCV. However, even different subclones and passages of this single cell line exhibit tremendous differences in HCV replication efficiency. By comparative gene expression profiling using a multi-pronged correlation analysis across eight different Huh7 variants, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…Interestingly, higher NR0B2 expression is a favorite factor for overall survival in patients with viral hepatitis history (Figure 2F), especially for those without alcohol consumption and Asian male patients. These data were supported by a previous report that SHP protein suppressed HCV replication in human liver cancer HuH7 cells (27).…”
Section: Nr0b2 Expression Is a Favorite Prognosis Factor In Liver Cancerssupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, higher NR0B2 expression is a favorite factor for overall survival in patients with viral hepatitis history (Figure 2F), especially for those without alcohol consumption and Asian male patients. These data were supported by a previous report that SHP protein suppressed HCV replication in human liver cancer HuH7 cells (27).…”
Section: Nr0b2 Expression Is a Favorite Prognosis Factor In Liver Cancerssupporting
confidence: 88%
“…Chronic viral hepatitis is a substantial contributing factor for liver cancer development and progression (51). HCV infection was shown to increase NR0B2 gene expression in human liver cells (52), and NR0B2 gene silencing or an excessive overexpression all reduced HCV replication in Huh7 cells (27). This study found an interesting correlation of NR0B2 expression with over survival in liver cancer patients with viral hepatitis history (HR = 0.52, p = 0.0416), which was more significant in Asian male patients (HR = 0.33, p = 0.0157).…”
Section: Discussionmentioning
confidence: 99%
“…THAP7 encodes a transcriptional repressor that acts via histone deacetylation [ 34 ]). Notably, THAP7 overexpression induces permissiveness of human hepatoma Huh7 cells to hepatitis C viral invasion [ 35 ]. These data suggest that both LZTR1 per se , as target genes affected by rs112544, may be involved in immune system function and anti-viral response.…”
Section: Discussionmentioning
confidence: 99%
“…2×10 5 Lunet-CD81 high [49] cells per 6-well were seeded in 2 mL 16 hours prior to infection. To ensure simultaneous infection of all cells, cells were kept at 4°C for 30 min before medium aspiration and inoculation with pre-cooled PEG-precipitated HCV cc (Jc1) [50] at an MOI of 1 at 4°C for one hour (1 mL per 6-well). The inoculum was removed and cells were covered with 1 ml per well pre-warmed (37°C) medium and incubated for one hour at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…A strand-specific RT-qPCR protocol was used to quantify numbers of (+)- and (-)-strand RNA per cell [52]. TCID50 of supernatants was measured and calculated as described previously [50] and converted to PFU/mL.…”
Section: Methodsmentioning
confidence: 99%